2008 Computers in Cardiology 2008
DOI: 10.1109/cic.2008.4749025
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cardiac arrhythmia using kernel difference weighted KNN classifier

Abstract: In this paper, we proposed a kernel differenceweighted k-nearest neighbor classifier (KDF-WKNN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…From the comparison chart shown in fig.3, it is observed that our neuro-genetic model outperformed on selected feature subset compared to full feature set. A novel pruning method [14 ] 68.47% Kernel Difference weighted KNN [15] 70.66% SVM with Gaussian Kernel [16] 76.10% Learning Vector Quantization [17] 76.92% Fuzzy weighted AIRS [18] 80.71% NN with weighted fuzzy membership function [19] 81.32% Modular Neural Network [20] 82.22% MLP with two hidden layers [21] 85.55% Proposed Neuro-Genetic Approach 89.58%…”
Section: Resultsmentioning
confidence: 99%
“…From the comparison chart shown in fig.3, it is observed that our neuro-genetic model outperformed on selected feature subset compared to full feature set. A novel pruning method [14 ] 68.47% Kernel Difference weighted KNN [15] 70.66% SVM with Gaussian Kernel [16] 76.10% Learning Vector Quantization [17] 76.92% Fuzzy weighted AIRS [18] 80.71% NN with weighted fuzzy membership function [19] 81.32% Modular Neural Network [20] 82.22% MLP with two hidden layers [21] 85.55% Proposed Neuro-Genetic Approach 89.58%…”
Section: Resultsmentioning
confidence: 99%
“…Compared to algorithms which utilized voting feature intervals, naive Bayes, k-nearest neighbors (KNN), support vector machines (SVM), and logistic regression, the model proposed here offers increased accuracy [6,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…NN's error rate has been proven to be asymptotically at most twice that of the Bayesian error rate [20]. NN has been used for image clustering [21] and cardiac arrhythmia diagnosis [22], and so forth, but few published researches can be found in machine fault detection. In this paper, the NN classifier is used to evaluate the reduced feature vectors by KPCA for avoiding relatively local relevance between parameters and reducing computation complexity.…”
Section: Multiclasses Fault Diagnosis -Nearest Neighbormentioning
confidence: 99%